Autonomic and perceptual responses to induction of a ketogenic diet in free-Living endurance athletes: a randomized, crossover trial - Maunder, E.; Dulson, D. K.; Shaw, D. M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Considerable interindividual heterogeneity has been observed in endurance performance responses following induction of a ketogenic diet (KD). It is plausible that a physiological stress response in the period following the dramatic dietary shift associated with transition to a KD may explain this heterogeneity.